The effect of luteal phase gonadotropin-releasing hormone antagonist administration on IVF outcomes in women at risk of OHSS Maryam - Maryam Eftekhar; Sepideh Miraj; Zahrasadat Mortazavifar (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Gonadotropin-releasing hormone (GnRH) plays essential roles in embryo implantation, invasion of trophoblastic tissue, and steroid synthesis in the placenta. Objective: The aim of this study was to evaluate the effect of GnRH antagonist administration on pregnancy outcomes in early implantation period. Materials and Methods: In this retrospective study, 94 infertile women undergoing GnRH antagonist protocol who were at risk of ovarian hyperstimulation syndrome (OHSS) were included. Sixty-seven patients (group I) received Cetrorelix 0.25 mg/daily in the luteal phase for 3 days while in 27 participants (group II), it was not administered. Pregnancy outcomes were assessed based on chemical and clinical pregnancy rates. Results: The pregnancy outcomes were not significantly different between two groups (p=0.224). Conclusion: The present study proposed that luteal phase GnRH antagonist administration does not influence the chance of successful pregnancy outcomes.